2022
DOI: 10.1007/s40609-022-00230-1
|View full text |Cite
|
Sign up to set email alerts
|

Locked Down: Economic and Health Effects of COVID-19 Response on Residents of a South African Township

Abstract: Background Little research has examined how pandemics affect residents in under-resourced communities. This study investigated how COVID-19 and lockdown policies affected residents of Alexandra, one of Johannesburg, South Africa’s lowest-income townships. Methods We conducted a telephone survey May 11–22, 2020, while the lockdown and alcohol ban were in effect, of a spatially stratified sample of 353 adult Alexandra residents drawn randomly from voter registration, cred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to Borofsky and Gu ¨nther (2022), pedestrian activity decreased by 48% and 61% in shared courtyards in urban areas in South Africa. Fisher et al (2022) found that formal settlements recorded loss of incomes, decline in food availability, decline alcohol use and increase in depression. This evidence highlights the neglect of informal settlements in fighting COVID-19 and, thus, the interconnected nature of governance, health and equity.…”
Section: Nature Of Informal Settlement Rental Housingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Borofsky and Gu ¨nther (2022), pedestrian activity decreased by 48% and 61% in shared courtyards in urban areas in South Africa. Fisher et al (2022) found that formal settlements recorded loss of incomes, decline in food availability, decline alcohol use and increase in depression. This evidence highlights the neglect of informal settlements in fighting COVID-19 and, thus, the interconnected nature of governance, health and equity.…”
Section: Nature Of Informal Settlement Rental Housingmentioning
confidence: 99%
“…According to Borofsky and Günther (2022), pedestrian activity decreased by 48% and 61% in shared courtyards in urban areas in South Africa. Fisher et al (2022) found that formal settlements recorded loss of incomes, decline in food availability, decline alcohol use and increase in depression.…”
Section: Nature Of Informal Settlement Rental Housingmentioning
confidence: 99%